2020
DOI: 10.1245/s10434-020-09390-w
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Impacts Prognosis of Patients Undergoing Curative-Intent Hepatocellular Carcinoma

Abstract: Background. The impact of tumor necrosis relative to prognosis among patients undergoing curative-intent resection for hepatocellular carcinoma (HCC) remains illdefined. Methods. Patients who underwent curative-intent resection for HCC without any prior treatment between 2000 and 2017 were identified from an international multi-institutional database. Tumor necrosis was graded as absent, moderate (\ 50% area), or extensive (C 50% area) on histological examination. The relationship between tumor necrosis, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…However, when we also included larger tumors outside the transplantation criteria, the correlation does not remain, because very large tumors are associated with a lower than expected reduction effect on magnesium levels. The explanation for this particular behavior of larger tumors could be that, as already demonstrated, large HCCs are associated with severe spontaneous necrosis of the lesions and therefore have fewer viable cells capable of internalizing Mg than those expected based on the size of the lesions 42 . Regarding the change in magnesemia after locoregional treatment, we did not find a relationship either with the total tumor volume before treatment or with the residual tumor tissue after therapy.…”
Section: Discussionmentioning
confidence: 75%
“…However, when we also included larger tumors outside the transplantation criteria, the correlation does not remain, because very large tumors are associated with a lower than expected reduction effect on magnesium levels. The explanation for this particular behavior of larger tumors could be that, as already demonstrated, large HCCs are associated with severe spontaneous necrosis of the lesions and therefore have fewer viable cells capable of internalizing Mg than those expected based on the size of the lesions 42 . Regarding the change in magnesemia after locoregional treatment, we did not find a relationship either with the total tumor volume before treatment or with the residual tumor tissue after therapy.…”
Section: Discussionmentioning
confidence: 75%
“…For example, Wei et al recently demonstrated the prognostic impact of tumor necrosis among 919 patients who underwent curative-intent resection for HCC. 12 In this study, tumor necrosis was a strong predictor of poor outcomes following HCC resection irrespective of T stage. 12 In another study, Atanasov et al demonstrated that tumor necrosis was the only independent prognostic factor among individuals with resected hilar cholangiocarcinoma (n = 47) after adjusting for other clinicopathologic characteristics.…”
Section: Discussionmentioning
confidence: 60%
“…12 In this study, tumor necrosis was a strong predictor of poor outcomes following HCC resection irrespective of T stage. 12 In another study, Atanasov et al demonstrated that tumor necrosis was the only independent prognostic factor among individuals with resected hilar cholangiocarcinoma (n = 47) after adjusting for other clinicopathologic characteristics. 27 The same group later reported on the impact of tumor necrosis among 88 patients with ICC in a single-center analysis.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations